The blue economy effects on EUROMED tourism: forecasting approach - Mai Mohamed Yasser; Yasser Tawfik Halim; Alaa A. Abd Elmegaly (Future Business Journal)
Abstract This study examines the factors that influence the blue economy in EUROMED, aiming at promoting economic growth in line with the UN Sustainable Development Goals. EUROMED was chosen because all of its nations have fisheries and marine tourism, which are the two key indicators of the blue economy. Blue economy contributes to sustainable development in the fisheries and marine tourism sectors. A commitment to sustainability has sped up national and regional blue economy policy development. The study uses secondary qualitative data and literature review to analyse the synergies and conflicts between EUROMED blue economy strategies and the UN Sustainable Development Goals. The findings suggest that GDP growth, aqua production, open trade, CO2 emissions, and inflation rate influence the blue economy, and that ecotourism that considers education, society, and the environment may generate sustainable fisheries and marine tourism. Only 21 countries gave the ARDL test between 2000 and 2019. This study analyses synergies and conflicts between EUROMED blue economy strategies and UN Sustainable Development Goals. Location-based contextual development of blue economies that suit all players' requirements is essential to maintain sustainability objectives. Ensure resilience against future environmental and political shocks, preserve the ecological underpinning for vibrant blue economies, and create capacity at all levels to promote effective and fair governance. This study tries to make good use of ocean conservation and aquaculture within the context of the blue economy. This is the first EUROMED blue economy study and contributes to the theoretical and methodological development of blue economy research.